Sistem Pendukung Keputusan Pemilihan Web Hosting Terbaik Menggunakan Metode ROC dan Metode WASPAS - Bella Putri Cahyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In Indonesia, there are several well-known hosting service providers such as Hostinger, Niaga Hoster and others. Each hosting provider has its own advantages both in terms of features and price offered, as well as providing additional features for free. Even so, users need to pay attention to some problems that may arise, such as problems with interrupted access and slow website speeds, limited storage capacity and low CPU, as well as security concerns. Therefore, in this study, researchers used decision-making techniques with decision support systems. In spk, of course there are many methods that are presented to the user so that the user can freely choose what method to use for solving each problem that occurs, the previous researcher has conducted a literature study on researchers who have conducted similar research on the research that I made, where there are several research conducted using only one application method, namely the WASPAS method, so of course it is less effective if the weighting of the importance level of the criteria is self-determined, so the researcher uses the WASPAS method as a ranking of 7 alternatives to be dissected and also uses the ROC method as a weighting method for 5 criteria in determine the best web hosting. The results showed that Niaga Hoster was the best choice with a final score of 0.9879, followed by Rumahweb with a final score of 0.9325, and Jagoan Hosting with a final score of 0.9184